2022
DOI: 10.3390/cancers14051249
|View full text |Cite
|
Sign up to set email alerts
|

Evolving Paradigms in the Systemic Treatment of Advanced Gallbladder Cancer: Updates in Year 2022

Abstract: Gallbladder cancer (GBC) is a biological, anatomical, and clinically distinct subset of biliary tract cancers (BTC), which also include extra- and intra-hepatic cholangiocarcinoma. The advent of next-generation sequencing (NGS) clearly shows that GBC is genetically different from cholangiocarcinoma. Although GBC is a relatively rare cancer, it is highly aggressive and carries a grave prognosis. To date, complete surgical resection remains the only path for cure but is limited to patients with early-stage disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 86 publications
0
8
0
Order By: Relevance
“…In this context, it had to be clarified that a real predictive role for this biomarker has been acknowledged for tumors of the esophagus, esophago–gastric junction and stomach [ 30 ]. Conversely, for intestinal cancers and for tumors of the pancreatobiliary system, PD-L1 has no recognized role in predicting the response to immunotherapy [ 30 , 31 , 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, it had to be clarified that a real predictive role for this biomarker has been acknowledged for tumors of the esophagus, esophago–gastric junction and stomach [ 30 ]. Conversely, for intestinal cancers and for tumors of the pancreatobiliary system, PD-L1 has no recognized role in predicting the response to immunotherapy [ 30 , 31 , 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…As the basis of biliary cancer treatment, adjuvant systemic therapy has been problematic for patients with GBC due to a dearth of clinical trials focused on this disease, with this being worse in GBASC for its even lower incidence (2,22,23). Akce et al (14) established a connection between increased survival with receipt of adjuvant systemic therapy in patients with GBASC.…”
Section: Survivalmentioning
confidence: 99%
“…In 2022, an estimated 12,130 GBC and other biliary cancers are expected to be diagnosed, with an estimated 4400 patients dying from these diseases. Prognosis is particularly poor in elderly and racial minorities [ 24 ]. Tan et al identified 24 differentially expressed proteins, which includes 12 upregulated and 12 downregulated proteins between gallbladder cancer patients and healthy controls [ 25 ].…”
Section: Aberrant Phosphorylation In Cancermentioning
confidence: 99%